Why him? [videorecording (DVD)] - Hamburg, John, 1970-; Cranston, Bryan, 1956-; Franco, James, 1978-; Deutch, Zoey, 1994-; Mullally, Megan (20th Century Fox Home Entertainment, 2017)
Over the holidays, Ned, an overprotective but loving dad and his family visit his daughter at Stanford, where he meets his biggest nightmare: her well-meaning but socially awkward Silicon Valley billionaire boyfriend, Laird. The rivalry develops, and Ned's panic level goes through the roof when he finds himself lost in this glamorous high-tech world and learns that Laird is about to pop the question.